Vezljivost glagolov védenja v zgodovini slovenskega knjižnega jezika - Grošelj, Robert (Slavia Centralis, 2020)
The valency of the verbs of knowing in the history of Slovenian literary language The paper discusses the development of valency for the verbs of knowing, i.e., umeti (with its secondary imperfective umevati), vedeti and znati, in the history of Slovenian literary language. In the study the verb meanings are defined, within every meaning the semantic and government patterns are determined. The patterns are analysed as to their stability, developmental characteristics, and competition with one another. Within every meaning the valency characteristics of the analysed verbs are compared.